Peripheral Tramadol in Dentistry: A New Use for an Old Drug - Chavarría DDS, MSc, PhD, Daniel; Pozos DDS, MSc, PhD, Amaury (Odovtos - International Journal of Dental Sciences, 2016)
Tramadol is a well known central acting analgesic drug, used in a wide variety of treatments within health sciences; including dentistry. Due to its lack of anti-inflammatory action and some adverse effects related mainly to opioid receptors agonism, it is not use as a routine alternative; keeping mainly for patients allergic to non-steroideal anti-inflammatory drugs or as an adjuvant to manage severe odontogenic pain. Since new available evidence supports the possible analgesic effect of this drug when is applied locally in different sites, recent reports have been done to explore the same effect in the orofacial region, especially to improve the local management of odontogenic pain. This new perspective article summarize some of the current efforts develop to explore the peripheral Tramadol in dentistry; “a new use for an old drug”.